Bryostatin-1 for latent virus reactivation in HIV-infected patients on antiretroviral therapy. (1st June 2016) - Gutiérrez, Carolina; Serrano-Villar, Sergio; Madrid-Elena, Nadia; Pérez-Elías, Maria J.; Martín, Maria Elena; Barbas, Coral; Ruipérez, Javier; Muñoz, Eduardo; Muñoz-Fernández, Maria Angeles; Castor, Trevor; Moreno, Santiago
Abstract : Objective: The protein kinase C (PKC) agonist bryostatin-1 has shown significant ex-vivo potency to revert HIV-1 latency, compared with other latency reversing agents (LRA). The safety of this candidate LRA remains to be proven in treated HIV-1-infected patients. Methods: In this pilot, double-blind phase I clinical-trial (NCT 02269605), we included aviraemic HIV-1-infected patients on triple antiretroviral therapy to evaluate the effects of two different single doses of bryostatin-1 (10 or 20 μg/m 2 ) compared with placebo. Results: Twelve patients were included, four in each arm. Bryostatin-1 was well tolerated in all participants. Two patients in the 20 μg/m 2 arm developed grade 1 headache and myalgia. No detectable increases of cell-associated unspliced (CA-US) HIV-1-RNA were observed in any study arm, nor differences in HIV-1 mRNA dynamics between arms ( P = 0.44). The frequency of samples with low-level viraemia did not differ between arms and low-level viraemia did not correlate with CA-US HIV-1-RNA levels ( P = 0.676). No changes were detected on protein kinase C (PKC) activity and in biomarkers of inflammation (sCD14 + and interleukin-6) in any study arm. After the single dose of bryostatin-1, plasma concentrations were under detection limits in all the patients in the 10 μg/m 2 arm, and below 50 pg/ml (0.05 nmol/l) in those in the 20 μg/m 2 arm. Conclusion: Bryostatin-1 was safe at the single doses administered. However, the drug did not show any effect on PKC activity or on the transcription of latent HIV, probably due to low plasma concentrations. This study will inform next trials aimed at assessing higher doses, multiple dosing schedules or combination studies with synergistic drugs.